2018
DOI: 10.1007/s12928-018-0523-z
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary critical limb ischemia: Asian multidisciplinary consensus statement on the collaboration between endovascular therapy and wound care

Abstract: The burden of peripheral artery disease (PAD) and diabetes in Asia is projected to increase. Asia also has the highest incidence and prevalence of end-stage renal disease (ESRD) in the world. Therefore, most Asian patients with PAD might have diabetic PAD or ESRD-related PAD. Given these pandemic conditions, critical limb ischemia (CLI) with diabetes or ESRD, the most advanced and challenging subset of PAD, is an emerging public health issue in Asian countries. Given that diabetic and ESRD-related CLI have com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…An Asian multidisciplinary consensus statement of contemporary CLI suggested that below-the-ankle intervention should only be considered if no clinical improvement with sufficient microcirculation is observed after above-the-ankle intervention (Kawarada et al 2018 ). Moreover, several clinical trials have reported that pedal artery disease is an independent predictor of delayed wound healing in CLI patients (Kawarada et al 2012 ; Shiraki et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…An Asian multidisciplinary consensus statement of contemporary CLI suggested that below-the-ankle intervention should only be considered if no clinical improvement with sufficient microcirculation is observed after above-the-ankle intervention (Kawarada et al 2018 ). Moreover, several clinical trials have reported that pedal artery disease is an independent predictor of delayed wound healing in CLI patients (Kawarada et al 2012 ; Shiraki et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic PAD, especially that resistant to conservative treatments, requires timely revascularization 4 , 10 , 11 ) , as does symptomatic CAD 12 ) . Recently, percutaneous technique has become increasingly popular in clinical practice, and endovascular procedures have markedly increased in volume 13 ) . Th e presentation pattern directly affects pressure on hospital beds and medical staffing.…”
Section: Introductionmentioning
confidence: 99%
“…The femoropopliteal (FP) artery is the most common site of PAD involvement. With technological improvements in the endovascular armamentarium, catheter-based FP intervention has gained popularity during the last decade [2][3][4][5][6][7]. Although the need for quantitative vessel analysis (QVA) for objective evaluation in FP intervention outcomes has been emphasized for over a decade [8], a standard methodology for assessing restenosis has yet to be established.…”
Section: Introductionmentioning
confidence: 99%